MEREKONSTRUKSI SIKLUS KEHIDUPAN SEBAGAI DAYA TARIK WISATA BUDAYA DI SAMSARA LIVING MUSEUM - Putu Guntur Pramana Putra; Ni Nyoman Arini; Komang Shintiya Nita Kristiana Putri (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2023)
Cultural tourism is a type of tourism that specifically conserves the various resources it uses, namely tourism that develops culture in a sustainable manner. Bali has wealth in the form of a variety of cultural arts, customs and traditions, and religious procedures and their existence as a legacy from the past. Cultural arts in Bali can live and develop influenced by various religious ceremonial activities. This study analyzed the reconstructing the cycle of life as a cultural tourism attraction in the Samsara Living Museum. This study aims to find out the destination branding and the life cycle of the Balinese people which are appointed as the concept of this samsara living museum. Data were collected through observation, in-depth interviews, and literature study. The data analysis used is descriptive qualitative. This study concludes that the Samsara Living Museum has sparked destination branding and has implemented the reconstruction of the Balinese life cycle as a cultural tourism attraction. Keywords : destination branding, balinese life cycle, samsara living museum